Probing How Flashcards and Teams Games Tournament Boost EFL Learners’ Vocabulary - Alvianti Aidarahma; Testiana Deni Wijayatiningsih; Siti Aimah (Universitas Muhammadiyah Metro, 2022)
This current study investigates the implementation of flashcards and the Teams Games Tournament (TGT) to enhance students' vocabulary mastery. The participants were SDIT Nurul Hidayah Cigedog Brebes, fourth graders in the academic year 2021-2022. In addition, thirty-three students were the subjects of the study. This study employed Classroom Action Research. Instruments included a pre-test, a post-test, a questionnaire, and an observation. Besides using the normality test, descriptive statistics and paired sample T-test were utilized to analyze the data. In cycle I, the pre-test average was 72.12, and the post-test average was 82.03. In cycle II, the pre-test and post-test standards increased from 85.67 to 93.061. The cycle I mean was more significant than the cycle II mean. The